Ogłoszenie upadłości a bieg terminu przedawnienia zobowiązania podatkowego - Nykiel, Włodzimierz; Sęk, Małgorzata (Kwartalnik Prawa Podatkowego, 2015)
Doubts and disputes concerning the interpretation and application of the rules governing the institution of limitation of tax liability often concern the limitation period itself, and especially the starting day of the limitation period, suspension and interruption thereof. The purpose of this article is to clarify one of these doubts: to determine whether the bankruptcy, which took place after the deadline for payment of the tax, but before the end of the calendar year in which the payment deadline expired, interrupts the limitation period. This requires a prior determination of when the period of limitation starts.